PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X PADA MAN 2 PIDIE JAYA TAHUN 2019 - Arizal Fahmi Fahmi (SINTESA: Jurnal Kajian Islam dan Sosial Keagamaan, 2020)
This study is entitled "The Implementation of Jigsaw Type Cooperative Learning Model to Improve Mathematics Learning Outcomes of Class X MAN 2 Pidie Jaya in 2019". This study aims to determine whether the application of a jigsaw cooperative learning model can improve student learning outcomes in mathematics learning in class X MAN 2 Pidie Jaya. This type of research is quantitative research. The design of this study is planning, design, implementation, evaluation, and reporting. Data analysis was performed descriptively. The results of the data analysis showed that the acquisition of the pre-test results of students 'mathematics learning with an average of 60. Furthermore, the researchers treated them by applying a jigsaw cooperative learning model for three meetings, at the end of the study the researchers gave a post-test evaluation to see the students' abilities after applying the cooperative learning model jigsaw. The results of data analysis showed that the acquisition of the pre-test results of students' mathematics learning with an average of 84.4. It can be concluded, the Jigsaw cooperative learning model can improve student learning outcomes, and the teacher always improves his expertise in using the Jigsaw cooperative learning model so that students are not bored and are more eager to follow the lessons and understand mathematics learning.